2018
DOI: 10.1080/00918369.2018.1547559
|View full text |Cite
|
Sign up to set email alerts
|

Does Contact Matter?: The Relative Importance of Contact in Predicting Anti-Gay Prejudice in Jamaica

Abstract: This study was conducted with the assistance of the organization J-FLAG. The Author declares that he has no conflict of interests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
(101 reference statements)
0
4
0
Order By: Relevance
“…By contrast, women, non-whites, and sexual minority respondents were, on average, less likely to agree that finding a mentally healthy romantic partner was important. Previous researchers have suggested that minority individuals (women, racial/ethnic minorities, LGBT) are more likely to be accepting of other minority individuals due to both contact hypotheses [55] and minority-stress experiences [56].…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, women, non-whites, and sexual minority respondents were, on average, less likely to agree that finding a mentally healthy romantic partner was important. Previous researchers have suggested that minority individuals (women, racial/ethnic minorities, LGBT) are more likely to be accepting of other minority individuals due to both contact hypotheses [55] and minority-stress experiences [56].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these two groups may encounter gay/lesbian Christians more frequently than nonreligious cisgender heterosexual people do (due to identity-related activities such as Pride or church events). This contact may raise more opportunities to act on biases toward gay/lesbian Christians, but it may also mitigate such biases over time (Herek & Capitanio, 1996; Lytle et al, 2017; West, 2020).…”
Section: Bias Against Gay and Lesbian Christiansmentioning
confidence: 99%
“…Examination of relations between legal rights and attitudes has also been largely limited to Western countries, which tend to be more institutionally supportive of LGBT people compared to many non-Western nations. Further, examination of personal rights support is particularly critical given that the amount of contact one has with gays/lesbians is associated with less anti-gay attitudes, but not with fewer anti-gay behaviours, in countries known to be intolerant towards gays and lesbians (West, 2020). Thus, it remains unclear whether LGBT contact can increase support for LGBT communities, beyond favourable attitudes or evaluations, in certain environments.…”
Section: Contextual Influence On Lgbt Rights Supportmentioning
confidence: 99%